The Jewel of Annual Astrology A Parallel Sanskrit-English Critical Edition of Balabhadra's Hāyanaratna - Gansten, Martin (Sir Henry Wellcome Asian Series, 2020)
The Jewel of Annual Astrology is an encyclopaedic treatise on Tājika or Sanskritized Perso-Arabic astrology, dealing particularly with the casting an interpretation of anniversary horoscopes. Authored in 1649 CE by Balabhadra Daivajña, court astrologer to Shāh Shujāʿ - Governor of Bengal and second son of the Mughal emperor Shāh Jahān - it casts light on the historical development of the Tājika school by extensive quotations from earlier works spanning five centuries. Readership: Anyone interested in the history of Indian astrology, the transmission of horoscopic astrology generally, the Indian reception of Perso-Arabic astral sciences, or intellectual history in early modern South Asia.